2009
DOI: 10.1002/hup.1075
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine treatment and improved cognitive functioning in borderline personality disorder

Abstract: In this study we have demonstrated that executive functioning in BPD is improved after treatment with quetiapine. Neurocognitive measures of executive functioning should be considered as valuable outcomes in the study of treatment efficacy in BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…The effect of quetiapine on response inhibition, a dimension of impulsivity, is consistent with previous literature on borderline personality disorder (BPD) patients (Hilger et al, 2003; Perrella et al, 2007; Van den Eynde et al, 2009). In previous research on individuals with BPD revealed that quetiapine decreased impulsivity, as captured through the BIS, a self-report measure.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of quetiapine on response inhibition, a dimension of impulsivity, is consistent with previous literature on borderline personality disorder (BPD) patients (Hilger et al, 2003; Perrella et al, 2007; Van den Eynde et al, 2009). In previous research on individuals with BPD revealed that quetiapine decreased impulsivity, as captured through the BIS, a self-report measure.…”
Section: Discussionsupporting
confidence: 89%
“…Quetiapine has been extensively studied over the years in several open-label trials of BPD patients [87][88][89][90][91][92], and the accumulated evidence suggested remarkable efficacy of this drug in reducing impulsiveaggressive behaviours, affective instability, and anxious-depressive symptoms.…”
Section: 2) Second Generation Antipsychoticsmentioning
confidence: 99%
“…Madame T. la frappait à grands coups jusqu'à ce qu'on ait recours à la force pour l'immobiliser. Dans le but de réduire l'impulsivité de madame T. et d'améliorer ses fonctions exécutives, un psychiatre de l'urgence lui prescrit de la quétiapine en monothérapie (Villeneuve et Lemelin, 2005 ;Van den Eynde et al, 2009). Du côté des séjours en psychiatrie, madame était gardée moins de soixante-douze heures à chaque hospitalisation.…”
Section: Histoire De Casunclassified